Squamous cell carcinoma of the middle rectum: Report of a case and literature overview. (2015) - Scaringi, Stefano; Bisogni, Damiano; Messerini, Luca; Bechi, Paolo
Highlights: We report a case of squamous cell carcinoma of middle rectum, with literature review ( International Journal of Surgery Case Reports 2014; 5: 86–90). The report we describe was characterized by the presence of a squamous cell carcinoma of the middle rectum and a synchronous ureteral tumor. The patient had undergone pelvic irradiation for prostate cancer seven years before, thus suggesting aforementioned treatment as possible cause. Abstract: INTRODUCTION: Squamous-cell carcinoma (SCC) of the middle rectum is a rare disease with an estimated incidence of 0.1–0.25/1000 colorectal neoplasms. Literature is represented essentially by case report and short series, and only seventy-six cases of colorectal squamous carcinoma have been documented in literature. PRESENTATION OF CASE: We report the case of a SCC of the middle rectum, associated to an ureteral inverted papilloma, occurred in a patient with a past history of prostate cancer treated with prostatectomy and radiotherapy. DISCUSSION: Colorectal squamous-cell carcinoma is a rare disease. This localization is more frequent than the right colon, but no more epidemiological informations are actually available apart from a slight predominance of the female sex. Risk factors for SCC of the rectum are unknown and many hypotheses have been evocated. Because of its rarity, the interpretation of available information is clouded by a lack of uniformity in diagnosis and treatment. CONCLUSION: Treatment of SCC remains very challenging, and the acquisition of more consistent data is needed.